Phytochemical And Pharmacological Evaluation Of Selected Medicinal Plant For Anti-Alzheimer’s Activity In Experimental Animals - Mani, Munesh; Sharma, Ritika; khan, Danish; F Mehta, Farhad; Saxena, Richa; Diwakar, Preeti Kumari; Sandeep, Waghulde; Kondrapu, Pydiraju (Journal of Neonatal Surgery, 2025)
As the world's population ages, Alzheimer's Disease (AD), the most common cause of dementia worldwide, becomes more common. Since AD is the main cause of dementia and neurodegenerative diseases, it is one of the biggest healthcare concerns of the twenty-first century. Dementia is the term used to describe an acquired loss of cognitive function across multiple cognitive domains. Understanding the mechanism of AD and available treatments may be aided by the animal experiments used in this study to ascertain whether chemical substances cause the disease. In this study, the Wistar albino rat was used to test the effectiveness of an Alcoholic Aerial Parts Extract of Dalbergia sissoo (AEDS) against scopolamine-induced Alzheimer's disease. Alcoholic extract was not harmful up to 2000 mg/kg body weight, according to the acute toxicity study. Rats were administered AEDS at 125 mg/kg body weight, 250 mg/kg body weight, and 500 mg/kg body weight, along with donepezil at a dose of 2.5 mg/kg. The Morris water maze, the Y-maze, the novel object recognition test, and biochemical tests such as the neurotransmitter acetylcholinesterase activity, catalase activity, malonyl dialdehyde, and nitric oxide assays were used to evaluate the anti-Alzheimer activity. Findings indicated that extracts prevent Alzheimer's disease and raise acetylcholine and catalase levels. Phytochemical research revealed that the AEDS contains phenolic chemicals, flavonoids, and alkaloids. The findings indicated that the presence of strong antioxidants such phenolic compounds, flavonoids, and alkaloids in the aerial sections of Dalbergia sissoo confers notable anti-Alzheimer activity.